Long-term Safety and Effectiveness of Hyaluronic Acid Fillers Correcting Nasolabial Folds in Chinese Patients - Yun Xie, MD; Sufan Wu, MD; Lei Wang, MD; Xiongzheng Mu, MD; Maoguo Shu, MD; Matthias Hofmann, PhD; Gudrun Klein, PhD; Qingfeng Li, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2023)
Background:. Soft-tissue fillers, specifically hyaluronic acid fillers, can reduce many signs of aging by treating the associated loss of subcutaneous fat and midfacial contour deficiencies. The objective of this study was to investigate whether the effectiveness and safety of Belotero Volume Lidocaine (BVL) compared with Restylane (RES, control) is noninferior in the treatment of severe nasolabial folds (NLFs) in Chinese patients. Methods:. This was a prospective, randomized, controlled, split-face clinical study. Overall, 220 Chinese patients of both sexes with symmetrical NLFs of severe intensity (grade 4) on the Wrinkle Severity Rating Scale (WSRS) were treated with both fillers. Treatment outcomes were assessed by the WSRS, and other scales, at multiple time points up to 18 months postinjection. The co-primary effectiveness outcomes were based on the blinded evaluator ratings of NLFs according to the WSRS scale after 6 and 12 months. Adverse events were assessed during the whole study and patients’ pain sensation at three time points after injection. Results:. Noninferiority of BVL versus control based on the WSRS was demonstrated at month 6 and month 12. Response rates were slightly higher for BVL than control at all time points, and BVL had a sustained effect until month 18. Pain sensation scores were significantly lower for BVL compared with control. The incidence rates of treatment-related AEs were low and very similar for both treatments. Conclusions:. This study demonstrates that BVL is a safe, long-lasting, and effective treatment to correct severe NLFs in Chinese patients while being noninferior to the control device.